Ethical Reflections on Proactive Health Issues from the Perspective of the Body Theory - Junrong LIU; Xu LU; Jiawen YANG (Yixue yu zhexue)
The body theory emphasizes the integrity and subjectivity of the body as well as individual experience and perception, reflecting that the body is not only a research object in the biological sense, but also a social and cultural construct. Health and disease have their specific social and cultural connotations. Proactive health has solid theoretical support and can be defended by ethical theories, conforming to the principles of body theory. Analyzing the issue of proactive health from the perspective of the body theory helps to deepen the understanding of proactive health, formulate personalized, widely participatory, and comprehensive health and wellness strategies, coordinate the conflicts of interest in health intervention, and better promote the realization of health equity and justice.